PENGARUH KECERDASAN EMOSIONAL DAN KECERDASAN SPIRITUAL TERHADAP KINERJA GURU DI MAN 1 KOTA MALANG, JAWA TIMUR - Tri Atma Budiantoro; Hadi Sunaryo; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACT            The purpose of this study was to discuss and analyze emotional intelligence, and spiritual intelligence on teacher performance in MAN 1 Kota Malang, East Java both partially and simultaneously or together. The population and sample used were all teachers in MAN 1 Kota Malang, East Java who collected 73 people. Data collection through questionnaires. Data analysis in this study used SPSS version 21. The sampling technique used a questionnaire with a scale scale rikert and data testing techniques used in this study using validity test, reliability test, normality test, classic assumption test, multiple linear regression analysis, F test and t test.            The results obtained from the evaluation and analysis show that emotional intelligence is positively insignificant towards teacher performance, while spiritual intelligence has a significant positive effect on teacher performance. Testing intellectual intelligence, and spiritual intelligence has a significant positive effect on teacher performance.Keywords: Emotional Intelligence, Spiritual Intelligence, Teacher Performance